Development of jute rope hybrid composite plate using carbon fibre - Nouri, K.; Alam, M.A.; Mohammadhassani, M.; Jumaat, Mohd Zamin; Abna, A.H. (2015)
Jute rope is one of the most popular materials used for composites in various industries and in civil engineering. This experimental study investigated two types of jute rope with different diameters for jute rope composite plates to determine the best combination of jute rope and carbon fiber in terms of ratio and physical and mechanical properties. Eight combinations of carbon fiber and jute rope with different percentages of carbon fiber were analyzed. Tensile tests for the jute rope composite plate and hybrid jute rope composite were conducted, and the mechanical and physical properties of the specimens were compared. Thereafter, the ideal combinations of jute rope with an optimum percentage of carbon fiber were identified and recommended. These particular combinations had tensile strengths that were 2.23 times and 1.76 times higher than other varieties in each type.